Epigenetic Modifications in T Cells: The Role of DNA Methylation in Salt-Sensitive Hypertension. Issue 2 (February 2020) - Dasinger, John Henry; Alsheikh, Ammar J.; Abais-Battad, Justine M.; Pan, Xiaoqing; Fehrenbach, Daniel J.; Lund, Hayley; Roberts, Michelle L.; Cowley, Allen W.; Kidambi, Srividya; Kotchen, Theodore A.; Liu, Pengyuan; Liang, Mingyu; et al.
Abstract : The SS (Dahl salt sensitive) rat is an established model of hypertension and renal damage that is accompanied with immune system activation in response to a high-salt diet. Investigations into the effects of sodium-independent and dependent components of the diet were shown to affect the disease phenotype with SS/MCW (JrHsdMcwi) rats maintained on a purified diet (AIN-76A) presenting with a more severe phenotype relative to grain-fed SS/CRL (JrHsdMcwiCrl) rats. Since contributions of the immune system, environment, and diet are documented to alter this phenotype, this present study examined the epigenetic profile of T cells isolated from the periphery and the kidney from these colonies. T cells isolated from kidneys of the 2 colonies revealed that transcriptomic and functional differences may contribute to the susceptibility of hypertension and renal damage. In response to high-salt challenge, the methylome of T cells isolated from the kidney of SS/MCW exhibit a significant increase in differentially methylated regions with a preference for hypermethylation compared with the SS/CRL kidney T cells. Circulating T cells exhibited similar methylation profiles between colonies. Utilizing transcriptomic data from T cells isolated from the same animals upon which the DNA methylation analysis was performed, a predominant negative correlation was observed between gene expression and DNA methylation in all groups. Lastly, inhibition of DNA methyltransferases blunted salt-induced hypertension and renal damage in the SS/MCW rats providing a functional role for methylation. This study demonstrated the influence of epigenetic modifications to immune cell function, highlighting the need for further investigations. Abstract : Supplemental Digital Content is available in the text.